Analisis Kinerja Keuangan Dengan Menggunakan Perhitungan Current Ratio (CR), Quick Ratio (QR), Gross Profit Margin (GPM) Dan Net Profit Margin (NPM) Pada Pt. Astra Internasional Tbk Periode 2018-2021 - Risya Afifatur Rahma; Indah Listyani; Edi Murdiyanto (STIKes Ibnu Sina Ajibarang, 2023)
This research aims to find out how good the financial performance is based on the current ratio, quick ratio, gross profit margin and net profit margin at PT Astra Internasional Tbk. The type of research used is quantitative descriptive. The data processed is PT Astra Internasional Tbk financial report data for the 2018-2021 period. The type of data used is secondary data. The data collection technique in this research is by copying financial report files. Technical data analysis uses quantitative descriptive methods with the formulas current ratio, quick ratio, gross profit margin and net profit margin. The results of this research show that the financial performance of PT Astra Internasional Tbk for the 2018-2021 period is reviewed from the current ratio, quick ratio, gross profit margin and net profit margin. So the author draws the conclusion that financial performance in terms of the current ratio and quick ratio is not good because the value is still below industry standards. Financial performance in terms of gross profit margin and net profit margin, the company's financial performance is also said to be not good because it is still below industry standards.